ICAO: HISTORICAL BACKGROUND, INSTITUTIONAL FRAMEWORK AND COMPETENCE - Vodolaskova, Kateryna; Holovko, Svitlana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of the study is a historical and law analysis of the historical background of the formation and development of the ICAO as well as a legal framework of its institutional framework and competence stipulated in the Chicago Convention. Research methods: the methodological background of this study includes methods of historicism, analytics, formal-dogmatic and systemic. Results: this year, the National Aviation University is celebrating its 90th anniversary since its official foundation, when the Kyiv Aviation Institute was founded on the basis of the Aviation Faculty of KMI by Decree of the Council of People’s Commissars of the USSR No. 1815 of 08/25/1933. However, in fact, the prerequisites for this official recognition and establishment were certain conditions based on enthusiasm, technical progress, the development of international civil aviation, and the need for a clear distinction between military and civil aviation. These and other conditions also became a condition for the creation of the ICAO – a specialized UN agency that organizes and coordinates international cooperation of states in all aspects of civil aviation. Discussion: this work is dedicated to research of the historical background, institutional framework, and competence of ICAO. These studies will also take contribution to the understanding of the conditions and background of formation and development of NAU in a more comprehensive way.